Biodegradation of heterocyclic hydrocarbon using biological activated carbon - Chia, Choon Hiung (Universiti Malaysia Sarawak (UNIMAS), 2013)
The disturbance on ecological system caused by environmental pollution has raised public concerns. Recently, heterocyclic hydrocarbon has been claimed as one of the major pollutants. Therefore, it is essential to develop an efficient system that is capable of degrading heterocyclic hydrocarbon. In this study, the positive Thalassospira Sp. Strain M02 that is capable of degrading specific substrate was selected and grew in ONR7a liquid medium supplemented with heterocyclic bydrocarbon. Activated carbon was introduced into the ONR7a medium together with the growth of bacteria to develop biological activated carbon. The detection of bacteria growth on activated carbon was carried out by serial dilution on every three days from day 0 to day 15. In the mean while, the degradation of carbazole was quantified by using Gas Chromatography-Mass Spechtrometry (GC-MS) method on every two days from day 0 to day 14. The colony forming units (CFU) in the log phase was higher and the carbazole was degraded to a lower concentration in the biological activated carbon unit as compared to control unit. As for the conclusion, the biodegradation of carbazole using biological activated carbon has shown to be more effective than the control unit by a difference of 94% degradation efficiency on day 12.